HUBUNGAN PERAN KEPALA RUANGAN DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT ADVENT MEDAN - Saragih, Masri; Bevy Gulo, Adventy Riang; Eva Kartika, Eva Kartika; Simbolon, Denry Cristiani (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The head ofoom as a manager must be able to guarantee the services provided by the implementing nurse in providing safe services and prioritizing patient comfort. The aim of this study was to determine the relationship between the role of the head of the room and the performance of nurses in the inpatient ward at Medan Adventist Hospital. The type of research used is qualitative research and descriptive correlation research design with a cross sectional approach. The research population used were all nurses in inpatient rooms with a total of 82 nurses. The sample in this study was 45 nurses using a purposive sampling technique. The instrument used is a questionnaire and will be analyzed using the Chi-Square test. The research results showed that the majority of room heads' roles were adequate (53.3%), the majority of nurses' performance was adequate (48.9%) and there was a significant relationship between the role of room heads and nurses' performance with a p value = 0.005. So it can be concluded that the better the role of the head of the room, the better the nurse's performance will be. So it is necessary to suggest that the head of the room can implement his role as head of the room to improve the performance of nurses.